The Effect of the Use of Activation 3D Mapping on the Patient X-Ray Load During Radiofrequency Ablation of Typical Atrial Flutter - Andriy V. Yakushev; Borys B. Kravchuk (Ukrainian Journal of Cardiovascular Surgery, 2024)
Supraventricular macro re-entry tachyarrhythmias occupy the leading places among all types of tachyarrhythmias. The most common in this category is typical atrial flutter (AFL). This heart rhythm disorder has a negative impact on the patients’ quality of life. Its complications can lead to disability and death due to possible thromboembolism. Therapeutic treatment is limited in effectiveness. The main method of intervention is catheter radiofrequency ablation (RFA). The standard approach of RFA of AFL is performed without the use of navigation systems under fluoroscopy guidance. However, this results in an increased radiation exposure to the patient and the medical personnel. Modern technologies in the field of invasive electrophysiology make it possible to create anatomical models of heart and reproduce the spread of electrical excitation. However, the routine use of additional navigation methods remains controversial.The aim. To compare the duration of RFA of typical AFL and radiation exposure with the use of anatomical and propagation mapping.Materials and methods. This study is based on the analysis of the treatment results obtained for 53 patients at the National Amosov Institute of Cardiovascular Surgery in the period from 2014 to 2023. Depending on imaging methods, the patients were divided into two groups. The first group included 27 patients with an anatomical mapping of the right atrium. The second group included 26 patients with propagation mapping.Results. In all the patients we have achieved a bidirectional conduction block through cavotricuspid isthmus. In the first group, the total duration of confirming the diagnosis and creating the anatomical model was 312 ± 26 seconds. The mean time to the moment of AFL termination and restoration of sinus rhythm was 230 ± 19 seconds. The average duration of the procedure was 41.5 ± 3.5 minutes, the average fluoroscopy time was 120 ± 10 seconds, the average dose area product (DAP) was 15 ± 1.3 Gy·cm2. In the second group, the average time for creating a 3D propagation model of right atrium and verifying the diagnosis was 748 ± 65 seconds. The average time from the first application to the termination of tachycardia was 227 ± 20 seconds. The average duration of the procedure was 55 ± 4.7 minutes, X-ray time was 93 ± 8 seconds, average DAP was 13 ± 1.1 Gy·cm2. The duration of the procedure in the second group was significantly longer (p = 0.03), however, the radiation exposure and DAP were not statistically different (p = 0.31) between the observation groups.Conclusions. The use of propagation mapping increases the time of the procedure by 24.5% and does not give a significant advantage in reducing the radiation exposure. The use of a navigation system during cavotricuspid isthmus RFA is recommended for concomitant radical treatment of complex supraventricular arrhythmias, such as atrial fibrillation.